DOP88 Long-term real-world data of ustekinumab in Crohn's Disease – the Stockholm ustekinumab study – STOCUSTE. (21st January 2022) - Bello, F; Lördal, M; Johansson, F; Sabhan, H; Muhsen, S; Borin, A; Forsberg, O; Wennerström, C; Söderman, C; Almer, S
Abstract: Background: Ustekinumab (UST), an anti-interleukin-12/23 antibody, has successfully been introduced in the treatment of IBD, mainly in patients failing anti-TNF-agents. The STOCUSTE study includes IBD patients treated with UST at four teaching hospitals in Stockholm to provide long-term follow-up data. Here, we report the outcome in Crohn's disease over the first 12 months. Methods: This retrospective study includes patients diagnosed with Crohn's disease and treated with UST who were followed until withdrawal of treatment for any reason, or until end of study, July 31, 2021. Disease activity (Harvey-Bradshaw Index (HBI); Physician Global Assessment (PGA), laboratory parameters and drug persistence were assessed. The primary outcome was remission (HBI ≤4; PGA = 0) and response (decrease HBI ≥3; PGA ≥1 from baseline) at 3 and 12 months, respectively. Results: 120 patients, 61 women (51%), with a median age of 27 (IQR 27) at start of UST were included. All patients had luminal disease and 19 (16%) also fistulizing disease. 109 (91%) had failed ≥1 and 59 (49%) ≥2 anti-TNF drugs. In addition, 50 patients (42%) failed vedolizumab. At inclusion, 106 (88%) had active disease; 40 (33%) were on corticosteroid treatment and 22 (18%) on thiopurines. The persistence on UST was high, 93% at 3 months and 56% at 12 months. Of patients on UST at 3 months, 38% were in remission, and, at 12 months, 53%. An additional 26% were in response at 12 months. Of the 40 patients initially on corticosteroids, 17 (43%) and 28 (70%) had stopped steroids at 3 and 12 months, respectively. The median faecal calprotectin level declined from 272 (90–1763) at baseline to 75 (49–99) µg/g at 3 months (p<0.01). There was a slight decrease in CRP over 12 months, from 3 (2–12) to 1 (1–2) mg/l, together with increases in haemoglobin and serum albumin (n.s). Withdrawal from treatment during the first 12 months was 44% (53/120), mainly due to persisting disease activity. Four patients were withdrawn due to adverse events, three needed bowel surgery, two had malignancy and one patient suffered from systemic infection. Conclusion: In this group of difficult-to-treat patients with Crohn's disease, UST was shown to be effective in the majority, with high drug persistence at 12 months in combination with a favorable safety profile.